Empowering Households and Individuals to Co-produce Positive Health Outcomes : For Equitable Care Amidst Rapid Growth and Urbanization - World Bank Group (World Bank, Washington, DC, 2019)
A move from the countryside to a metropolis can offer new opportunities, but it can also expose an individual to new lifestyles and behaviors that put health at risk. Increased rates of behavioral risk factors like smoking, alcohol use, obesity, sedentary lifestyle, unsafe driving, and sexual risk behavior are driving a triple burden of chronic conditions, infectious disease, and injuries. Once developed, effective management of these conditions requires patients to adhere to long-term treatment, and often with poor results. For a safe and healthy transition to urban living, individuals need multisectoral support to steer clear of health-harming traps while taking control of their own health care journeys.